Desert Dust, Industrialization, and Agricultural Fires: Health Impacts of Outdoor Air Pollution in Africa. Issue 7 (10th April 2019) - Bauer, Susanne E.; Im, Ulas; Mezuman, Keren; Gao, Chloe Y.
Abstract: The African continent continuously experiences extreme aerosol load conditions, during which the World Health Organization clean air standard of 10 μg/m 3 of PM2.5 mass is systematically exceeded. Africa holds the world largest source of desert dust emissions, undergoes strong industrial growth, and produces approximately a third of the Earth's biomass burning aerosol particles. Sub‐Saharan biomass burning is driven by agricultural practices, such as burning fields and bushes in the postharvest season for fertilization, land management, and pest control. Thus, these emissions are predominantly anthropogenic. Here we use global atmospheric composition, climate, and health models to simulate the chemical composition of the atmosphere and calculate the mortality rates for Africa by distinguishing between purely natural, industrial/domestic, and biomass burning emissions. Air quality‐related deaths in Africa rank within the top leading causes of death in Africa. Our results of ~780, 000 premature deaths annually point to the extensive health impacts of natural emissions, high mortality rate caused by industrialization in Nigeria and South Africa, and a smaller extent by fire emissions in Central and West Africa. In Africa, 43, 000 premature deaths are linked to biomass burning mainly driven by agriculture. Our results also show that natural sources, in particular windblown dust emissions, have large impacts on air quality and human health in Africa. Key Points: Air pollution in Africa leads to the premature death of about 800, 000 people per year Air quality‐related deaths rank within the top leading causes of death, possibly more than HIV/AIDS African continent‐wide, mineral desert dust is the main contributor to mortality, followed by "industrial/domestic" and biomass burning